2018
DOI: 10.1007/s00402-018-3090-y
|View full text |Cite
|
Sign up to set email alerts
|

Return to activity following revision total hip arthroplasty

Abstract: Return to activity following revision total hip arthroplasty Background: Demand for revision total hip arthroplasty (RTHA) continues to grow worldwide and is expected to more than double within the next 1-2 decades. The primary aim of this study was to examine return to function following revision THA in a UK population. Patients & methods: We assessed 118 patients (132 RTHAs, mean age 65 years SD 13, range 23 to 88) at a mean follow-up of 7.9 years (SD 4.4) postoperatively. Preoperative age, gender, BMI, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
18
1
Order By: Relevance
“…78% of patients receiving revision THA rated their function as better 1 year postoperatively. This is in accordance with another study reporting that 79% of patients undergoing revision surgery in the hip joint were satisfied or very satisfied with their surgical results almost 8 years after surgery (16).…”
Section: Discussionsupporting
confidence: 92%
“…78% of patients receiving revision THA rated their function as better 1 year postoperatively. This is in accordance with another study reporting that 79% of patients undergoing revision surgery in the hip joint were satisfied or very satisfied with their surgical results almost 8 years after surgery (16).…”
Section: Discussionsupporting
confidence: 92%
“…Herman et al also reported that PROMs (SF12- PCS, Harris Hip Score, and WOMAC) for the infection cohort were significantly worse than the noninfected controls [ 41 ]. Other previous studies have shown poor PROMs for revision THA due to dislocation or periprosthetic fracture and infection [ 41 , 42 ]. Turnbull et al reported that revision THA for aseptic loosening was associated with better PROMs (OHS and UCLA activity score) at 7-year follow-up, while revision for periprosthetic fracture had the worst PROMs and recurrent dislocation was associated with lower patient satisfaction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies have shown poor PROMs for revision THA due to dislocation or periprosthetic fracture and infection [ 41 , 42 ]. Turnbull et al reported that revision THA for aseptic loosening was associated with better PROMs (OHS and UCLA activity score) at 7-year follow-up, while revision for periprosthetic fracture had the worst PROMs and recurrent dislocation was associated with lower patient satisfaction [ 42 ]. There are no previous reports comparing PROMs between revision and re-revision THA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 180 000 patients therefore require total joint replacement surgery in the UK annually, a major operation which can result in incomplete satisfaction and residual symptoms, particularly in younger patients [160][161][162][163]. A rising number of patients also face the prospect of requiring revision joint replacement, a technically more complex and costly procedure with generally inferior clinical results [164][165][166][167][168][169]. Extensive efforts have therefore been made to search for novel and alternative strategies to aid and promote cartilage repair.…”
Section: Limitations Of Current Treatment Optionsmentioning
confidence: 99%